2006
DOI: 10.1111/j.1365-4632.2006.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of epidermodysplasia verruciformis and review of the literature

Abstract: Radiotherapy applied against the SCC previously, together with sunlight exposure may cause early malignant transformation of skin lesions and the destructive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 19 publications
1
63
0
11
Order By: Relevance
“…However, invasive and large tumors need a surgical wide excision either with or without regional lymph node dissection and postoperative RT. It is reported that EV patients receiving RT for SCC demonstrate both earlier promotion of skin cancer and more destructive disease [18]. In terms of survival rate, however, improvements have been demonstrated in patients who had a combination of surgery and RT compared to surgery alone for treatment of locally advanced SCC involving the maxillary sinus [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, invasive and large tumors need a surgical wide excision either with or without regional lymph node dissection and postoperative RT. It is reported that EV patients receiving RT for SCC demonstrate both earlier promotion of skin cancer and more destructive disease [18]. In terms of survival rate, however, improvements have been demonstrated in patients who had a combination of surgery and RT compared to surgery alone for treatment of locally advanced SCC involving the maxillary sinus [19].…”
Section: Discussionmentioning
confidence: 99%
“…The malignant transforma on of EV lesions into Squamous Cell Carcinoma occurs in 30-70% cases; this may require over 20 years for such conversion or occurs when the lesions have been present for 10 years or so, or usually in third and fourth decades of life. [12][13] Immunological changes occur in pa ents with this disease, especially in their cellular immunity. These pa ents show a defect of cell-mediated immunity that is specifi c toward the causa ve HPVs.…”
Section: Discussionmentioning
confidence: 99%
“…14 The dysplas c and malignant changes in the EV lesions usually occur in the form of ac nic keratosis, Bowen's disease or Squamous cell carcinoma having a low metasta c poten al. 12 However, all types of lesions seen in EV pa ents should be subjected to histopathology for early detec on of any malignant changes, as clinically benign appearing lesions can demonstrate atypia. Early iden fi ca on and appropriate treatment of ac nic keratoses is also important as these are increasingly being recognized as an early clinical manifesta on of biological con nuum that may ul mately lead to invasive Squamous cell carcinoma.…”
Section: 8mentioning
confidence: 99%
“…These drugs can however have several beneficial effects, including antiviral and antiproliferative action of tumor cells. 6,9,[11][12][13][14][15] Interferons have been used effectively for the treatment of warts in EV, with their antiviral action and ability to inhibit malignant cell growth and stimulate natural killer cells and T cells. 6,12,13 Genetic counseling and frequent dermatologic monitoring of patients should be undertaken.…”
Section: Mailing Address / Endereçomentioning
confidence: 99%
“…Epidermodysplasia verruciformis is a rare disease, first described by Lewandowski and Lutz in 1922, characterized by susceptibility to infections caused by human papillomavirus (HPV), beta-papillomavirus (HPV 5,8,9,12,14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25). It is a rare autosomal recessive genodermatosis, with cases linked to chromosome X.…”
Section: Introductionmentioning
confidence: 99%